Therapeutic index of inhaled corticosteroids in asthma: A dose–response comparison on airway hyperresponsiveness and adrenal axis suppression. Issue 2 (17th June 2020) - Daley‐Yates, Peter; Brealey, Noushin; Thomas, Sebin; Austin, Daren; Shabbir, Shaila; Harrison, Tim; Singh, Dave; Barnes, Neil
Abstract : Aims: To compare the airway potency, systemic activity and therapeutic index of three inhaled corticosteroids that differ in glucocorticoid receptor binding affinity, physicochemical and pharmacokinetic properties. Methods: This escalating‐dose, placebo‐controlled, cross‐over study randomised adults with asthma to 1 or 2 treatment periods with ≥25 days washout in‐between. Each treatment period comprised five 7‐day dose escalations (μg/d): fluticasone furoate (FF; 25 → 100 → 200 → 400 → 800), fluticasone propionate (FP; 50 → 200 → 500 → 1000 → 2000), budesonide (BUD; 100 → 400 → 800 → 1600 → 3200) or placebo. Airway hyperresponsiveness to adenosine‐5'‐monophosphate (AMP PC20 ) was assessed on day 8. Plasma cortisol was assessed on day 1 (predose baseline) and from pre‐PM dose on day 6 to pre‐PM dose day 7 (24‐h weighted mean). Results: Fifty‐four subjects were randomised. FF showed greater airway potency than FP and BUD (AMP PC20 dose at which 50% of the maximum effect is achieved [ED50 ] values: 48.52, 1081.27 and 1467.36 μg/d, respectively). Systemic activity (cortisol suppression) ED50 values were 899.99, 1986.05 and 1927.42 μg/d, respectively. The therapeutic index (ED50 cortisol suppression/ED50 AMP PC20 ) was wider for FF (18.55) than FP (1.84) and BUD (1.31). FF 100 μg/d and 200 μg/d were both comparable in terms of airway potency with high doses of FP (≥1000 μg twice daily [BID]) and BUD (≥1500 μg/BID). The systemic activity of FF 100 μg/d and 200 μg/d (cortisol suppression: 7.41% and 14.28%, respectively) was comparable with low doses of FP (100 μg/BID and 250 μg/BID) and BUD (100 μg/BID and 200 μg/BID). Conclusion: This study provides evidence that FF can provide more protection against airway hyperresponsiveness, with less systemic activity, than FP or BUD. This suggests that all inhaled corticosteroids are not therapeutically similar and may differ in their therapeutic index. (203162; NCT02991859).